KARAKTERISTIK TANAH LIAT DAN PENGARUHNYA TERHADAP KEBERHASILAN WARNA GLASIR - Prima Yustana (Corak : Jurnal Seni Kriya, 2012)
This eksperiment attempts to solve common problems faced in ceramic finish, finishingceramic objects have differences to resolve other matters. Glaze is a type of glass coating thatis applied to coat the ceramic objects, this is an interesting layer to be studied, because thesuccess glaze applications in ceramics is influenced by many factors. Applications glaze onceramic objects have a very high level of difficulty, the difficulty seen in glaze formulas,application techniques, firing temperature, shrinkage of dry matter and the successfulachievement of color after glaze the combustion process. This research is to determine whetherthe clay character has an influence on the success rate of the color will appear. The problemsolving method uses the experimental method, this method is considered more appropriate todetermine the level of success of an experiment relating to material containing chemicalelements.Clay used is a type of stoneware clay has five classes of characters, clay are as follows:1. Pacitan soil, wet soil has a reddish color, 2. Singkawang soil, wet soil has a whitish colour, 3.Sukabumi is a brightly colored ground, wet floor is a beige, with 4. Sukabumi, the dark ground,wet soil has a dark brown color, 5. Bojonegoro soil, wet soil has a light brown color. color Glazefive characters shall be applied on the surface of clay are: 1. young Greens, 2. Pink, 3. Greenishblue, 4. Brown 5. Dark blue.Character clay is relatively large contribution to the emergence of color glaze inaccordance with the wishes or the plan, especially when using a formula based on the glossyglaze. Glaze formula will tend to be stable when there is a combination of stain with a glazeoxide, stable formula can also be found on the matt glaze, because it glaze was close or nottransparent. coloring oxides are very sensitive to the character of soil temperature change iscobalt and fe ,experiment that required in advance if the formula contains two types of oxideglaze. Burning with the reduction or oxidation also will give effect to the glaze colors willappear.Keyword: experiment, color glaze, characters clay.